Effects of Andrographolide on Mouse Intestinal Microflora Based on High-Throughput Sequence Analysis - Wu, Haigang; Wu, Xian; Huang, Li; Ruan, Chongmei; Liu, Jinni; Chen, Xiaoqing; Liu, Jicheng; Luo, Houqing (Frontiers in Veterinary Science, 2021)
The intestinal flora is a micro-ecosystem that is closely linked to the overall health of the host. We examined the diversity and abundance of intestinal microorganisms in mice following the administration of andrographolide, a component of the Chinese medical herb Andrographis paniculata. Administration of andrographolide produces multiple beneficial effects including anti-inflammatory, antiviral and antibacterial effects but whether it directly influences the gut microbiota is not known. This study investigated whether the oral administration of andrographolide influences the intestinal microbiota and was compared with amoxicillin treatment as a positive control and water only as a negative control. We examined 21 cecal samples and conducted a high-throughput sequencing analysis based on V3-V4 variable region of the 16S rDNA genes. We found that the diversity and abundance of mouse gut microbiota decreased in direct proportion with the amoxicillin dose whereas andrographolide administration did not affect intestinal microbial community structure. The composition of intestinal microbes following andrographolide treatment was dominated by the Firmicutes while Bacteroidetes dominated the amoxicillin treatment group compared with the negative controls. Specifically, the f__Lachnospiraceae_ Unclassified, Lachnospiraceae_ NK4A136_group and Ruminococcaceae_ UCG-014 were enriched with andrographolide administration while Bacteroides, Klebsiella and Escherichia-Shigella significantly increased in the amoxicillin test groups. Amoxicillin administration altered the microbial community composition and structure by increasing the proportion of pathogenic to beneficial bacteria whereas andrographolide administration led to increases in the proportions and abundance of beneficial bacteria. This study provides a theoretical basis for finding alternatives to antibiotics to decrease bacterial resistance and restore intestinal floral imbalances.